Caracterisation chimique et evaluation des nutriments de certaines sources vegetales d'aliments proteiques tanzaniens - Jagadi, M.M.; Rundgren, M.; Ogle, R.B. (1987)
Evaluates the nutrient content of five Tanzanian plant protein feedstuffs, viz, untoasted red beans, cowpea seeds, kapok seed expeller cake, and sunflower seed expeller cake. Compares their protein quality with soya bean meal.